Optimasi proses finishing kulit ikan nila (Oreochromis niloticus) untuk bagian atas sepatu - Emiliana Kasmudjiastuti (Majalah Kulit, Karet, dan Plastik, 2014)
The aims of this study was to get the optimum finishing formulations of tilapia fish skin for shoe upper. The variations of experiment were four factors, namely of the variation of binders (1:2 and 1:3), lacquer water (1:1 and 1:2), plating temperatures (50, 65, 80 and 95°C) and plating time (0.5, 1, and 1.5 seconds). Testing was conducted on tensile strength, elongation at break, tear strength, stitch strength, softness, and colour fastness. Statistical analysis was conducted using the General Linear Model (GLM) followed by Tukey’s Studentized Range Test (TSRT). The results showed that the optimum formula for finishing were performed by a variation of binder 1:2, lacquer water 1:2, temperature of plating 95°C and time of plating 1.5 seconds, and it was characterized by the physical properties of tensile strength 177.32 kg/cm2, elongation at break 62%, tear strength 41.92 kg/cm, stitch strength 113.06 kg/cm, softness 2.33 and generally met the standard requirements of SNI 0253:2009: Footwear upper leather - goat skin.